Growth of Vertically Aligned ZnO Nanowires on Iron Oxide Layer - PPKBSM, Pusat Pengajian Kejuruteraan Bahan & Sumber Mineral (2012)
A low cost and substrate-independent method has been established to synthesize vertically aligned ZnO nanowires (NWs) on iron oxide films coated silicon substrates via low pressure Chemical Vapor Deposition (CVD) method at 650oC.